Ceramics of Power and Identity: The Ìjẹ̀bú Palace Assemblage in the Context of Yoruba Regional Networks - Olanrewaju Lasisi; Robin Garcia (Lakhomi Journal Scientific Journal of Culture, 2025)
This study examines the ceramic assemblage from the Ìjẹ̀bú royal palace, a key archaeological dataset for understanding material culture, identity, and regional interaction at a Yorùbá frontier polity. Drawing on the analysis of over 22,000 ceramic sherds recovered from controlled excavations at the palace’s sacred precinct, the paper situates Ìjẹ̀bú ceramics within the broader framework of Yorùbá ceramic spheres while highlighting their distinctive characteristics. Quantitative analysis reveals a marked dominance of bowls (approximately 88%) over jars (12%), underscoring the palace’s functional emphasis on feasting, ritual consumption, and sacred hospitality rather than storage or redistribution. While vessel forms and decorative motifs—including applied bosses, cordons, grooves, punctates, and striations—reflect participation in regional ceramic traditions linked to Ife and Oyo, Ìjẹ̀bú ceramics are distinguished by their frequent integration of multiple motifs on single vessels, the use of carved wooden roulettes rather than twisted-string variants, and the unique presence of bronze-sheeted pottery. These features suggest a locally distinctive material tradition that creatively recombined regional styles and introduced technological and symbolic innovations. The Ìjẹ̀bú assemblage is best understood as a regionally distinctive variant or sub-complex within the Yorùbá ceramic sphere system, reflecting the kingdom’s political autonomy, cultural hybridity, and negotiated identity at the intersection of major regional networks. The findings invite a reconsideration of ceramic sphere theory and foreground the dynamic role of frontier polities in shaping the material landscape of precolonial Yorùbáland.